La rapprochement sexuel en counseling et en psychothérapie: validité clinique des résultats de recherche - Valiquette, Marie; Sabourin, Stéphanie (Canadian Journal of Counselling and Psychotherapy, 2011)
This article examines the variability of the psychological sequelae observed in women after sexual involvement with their therapist and also the degree of clinical significance of the results observed. The clinical validity index allows examination of the extent of the changes that have taken place for each of the subjects and the percentage of cases where psychological functioning has improved or deteriorated from the beginning to the end of the psychotherapy. Fifty-one of these clients were recruited through the mass media and 25 more came as clients from the Service de psychologie de l'Université de Montréal. The clients complete the index of psychiatrie symptoms and the self-esteem scale. The analysis of the clinical validity of the results infers that the sexual intimacy during psychotherapy is associated with serious psychological sequelae for a high percentage of the subjects. The presence of chronic psychological sequelae can also be found, but to a lesser degree. The sexual intimacy is to be proscribed in the psychotherapy even though a small percentage of the clients seem to gain from that interaction.